Characterizing in vitro propagation and radiation response of murine mammary stem cells - Magers, Tonya Sirisalee, author; Ullrich, Robert L., advisor (Colorado State University. Libraries, 2009)
Stem cells in breast tissue may be sensitive to known carcinogens (i.e. ionizing radiation), which impact their susceptibility to transformation. The involvement of mammary stem cells in tumorigenesis could explain the heterogeneity and molecular complexity of breast cancer. However, the involvement and the underlying mechanisms of such targets have yet to be fully elucidated. This study was designed to investigate mammary stem cells as plausible targets of radiation-induced damage in radiation-induced mammary carcinogenesis. We utilized an in vitro system (mammospheres) that was developed for the detection of mammary stem cells. We expanded the applicability of this in vitro assay through the development of a methodology and novel size criteria to address specific radiation biology endpoints. We applied the methodology and size criteria to analyze the effects of ionizing radiation (IR) on the survival of mammary stem cells derived from mice carrying one mutated copy of Atm. Our results demonstrated that mammary stem cells derived from Atm-ΔSRI heterozygous mice (Atm(+/ΔSRI)) do not exhibit increased radiation sensitivity compared to their wildtype littermates (Atm(+/+)). In fact, mammary stem cells derived from Atm-ΔSRI heterozygous mice exhibited increased radioresistance. To our knowledge, this is the first study to examine the radiation response of mammary stem cells as mammospheres using Atm heterozygous mice carrying a known missense mutation found in human A-T. These studies demonstrated the proof of principle for this model development and the utility of this methodology. Our improved methodology has expanded the feasibility and the applicability of this model to examine numerous functional in vitro endpoints. We believe the methodology described here will facilitate investigating the radiation response of mammary stem cells and their progeny, and key components involved in early events of the carcinogenic process in murine model systems.
Keywords: mammary stem cells; radiation response; radiosensitivity; stem cells; molecular biology; medical imaging; medicine; oncology